Enhanced CO2 response of La1-xFeO3-δ perovskites with A-site deficiency synthesized by flame spray pyrolysis. Issue 1 (1st January 2023) - Jiao, Anqi; Zhang, Yiran; Yang, Lin; Zhao, Xuteng; Wu, Chunping; Chen, Ting; Zhan, Reggie; Huang, Zhen; Lin, He
Abstract: Measuring the CO2 concentration is the base of carbon accounting which aims to abate the greenhouse gas emission. This paper pays attention to developing sensitive material for CO2 detection in vehicle exhaust. For this purpose, La1-x FeO3-δ nanoparticles with A-site deficiency were synthesized by flame spray pyrolysis (FSP). The dynamic response of the prototype CO2 sensors was evaluated by checking the gas-mixture with 5%–15% CO2 . It was observed that the amount of A-site deficiency would obviously affect the performance of the material. La0.95 FeO3-δ sensor exhibits the highest response (S = 3.38) and a relatively short response time (t90 = 114s) among the serial La1-x FeO3-δ sensors (x = 0, 0.02, 0.05, 0.07 and 0.1). The improvement of the response might be attributed to the increase of oxygen vacancies and the higher valence of B-site cations caused by the introduction of A-site deficiency. Furthermore, the sensor exhibited good selectivity against NH3, NO, NO2 and CO, as well as good repeatability. However, water vapor is still a disturbance in the response. The response at 40% RH and 80% RH are 2.11 and 1.73, respectively. Finally, the sensing mechanism based on the participation of the oxygen vacancies was discussed.